Hormonal contraception as a method of social adaptation of women in modern society - Tatyana Yu Pestrikova; Elena A Yurasova; Igor V Yurasov; Tamara D Kovaleva (IP Berlin A.V., 2019)
Relevance. Currently, women make up more than 40% of the global workforce and more than half of students studying at universities around the world. Women's education, especially at a high level, tends to increase female employment. The mismatch of the style and rhythm of modern life with a genetically determined and working millennium reproductive program requires the choice of a specific approach to social adaptation. Aim. Analysis of literary sources on the use of hormonal contraception as a method of social adaptation. Materials and methods. To write this review, domestic and foreign publications were searched in Russian and international search systems (PubMed, eLibrary, etc.) for the last 2-10 years. The review included articles from peer-reviewed literature. Results. The review describes the features of modern hormonal contraceptives. Their non-contraceptive effects are presented. The individual non-contraceptive effects of a combined oral contraceptive containing 30 mg of ethinyl estradiol and 2 mg of chlormadinone acetate were determined. It has been established that the use of this contraceptive helps to improve the well-being and mood of patients, which allows you to actively use this contraceptive in routine clinical practice with premenstrual syndrome, dysmenorrhea, without the use of analgesics. Conclusions. The numerous positive effects of ethinyl estradiol and chlormadinone acetate allow the use of the drug as a means to increase social adaptation, and, consequently, improve the quality of life.